Analisis Fonologis Bahasa Serawai pada Mahasiswa Program Studi Tadris Bahasa Indonesia Universitas Islam Negeri Fatmawati Sukarno Bengkulu - Lestari, Siti Wahyu; Adisel; Welti Wediasti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the phonological forms of the Serawai language used by students of the Indonesian Language Education (Tadris Bahasa Indonesia) Study Program at the State Islamic University of Fatmawati Sukarno Bengkulu. The focus of this research includes the types of sound changes found in the speech of native Serawai-speaking students, which consist of assimilation, diphthongization, and phonological contraction. The method used is a qualitative descriptive approach with data collected through in-depth interviews, direct observation, and recordings of students’ daily conversations. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that there are three main phonological phenomena in the Serawai language used by students: 1) assimilation found in 24 words, indicating sound adjustment influenced by the surrounding phonetic environment; 2) diphthongization found in 49 words, with au being the most dominant diphthong, reflecting the interaction between Serawai and Indonesian; and 3) phonological contraction found in 17 words as a form of utterance simplification for communication efficiency. In conclusion, the phonology of the Serawai language used by Indonesian Language Education students is dynamic and adaptive to social and academic changes. Students play an essential role in preserving and developing the Serawai language through their speech practices that maintain the distinct phonological characteristics of their regional language. keywords: phonological analysis, serawai language, Indonesian language education study program students